An Acid-Mediated Multicomponent Domino Reaction for the Synthesis of N-Substituted Isoindolinones - Karu, Sudheer Kumar; Veludandi, Meghanath; Malapaka, Chandrasekharam (Synthesis, 2024)
A one-pot multicomponent reaction of 2-carboxybenzaldehyde, nitriles/anilines and a nucleophile (N,N-disubstituted anilines) for the synthesis of a range of functionalized N-substituted isoindolinone derivatives is described. This metal-free intramolecular cyclization reaction furnishes the desired products in good to excellent yields. The process is environmentally friendly and offers a sustainable method for synthesizing a diverse library of N-substituted isoindolinone derivatives under acidic conditions. This cascade reaction triggers the formation of a C–C and two C–N bonds involving carbonyl and carboxyl groups in the presence of nitriles/anilines. Additionally, in the absence of a nitrogen source, 3-substituted isobenzofuran-1(3H)-ones are synthesized.
Keywords: isoindolinones; isobenzofuranones; domino reaction; multicomponent reaction; atom economy; step economy